2017
DOI: 10.1371/journal.pone.0171577
|View full text |Cite
|
Sign up to set email alerts
|

Efficient decellularization for tissue engineering of the tendon-bone interface with preservation of biomechanics

Abstract: Interfaces between tendon/ligament and bone (“entheses”) are highly specialized tissues that allow for stress transfer between mechanically dissimilar materials. Entheses show very low regenerative capacity resulting in high incidences of failure after surgical repair. Tissue engineering is a promising approach to recover functionality of entheses. Here, we established a protocol to decellularize porcine entheses as scaffolds for enthesis tissue engineering. Chemical detergents as well as physical treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 60 publications
2
46
0
Order By: Relevance
“…This result is consistent with recently published work that showed intact tissue morphology in trachea decellularized under 1 Torr negative pressure, a stronger vacuum than used in our study (Butler et al, ). Athough we did not specifically test the effects of negative pressure on increasing efficiency of decellularization, a recent study using an SDS‐based method to decellularize trachea under 200 mmHg pressure compared to atmospheric pressure suggested they could reduce the treatment time from 72 to 48 hr while obtaining high decellularization efficiencies, which corroborates our anecdotal observation that negative pressure speeds decellularization (Xu et al, ).…”
Section: Resultssupporting
confidence: 77%
“…This result is consistent with recently published work that showed intact tissue morphology in trachea decellularized under 1 Torr negative pressure, a stronger vacuum than used in our study (Butler et al, ). Athough we did not specifically test the effects of negative pressure on increasing efficiency of decellularization, a recent study using an SDS‐based method to decellularize trachea under 200 mmHg pressure compared to atmospheric pressure suggested they could reduce the treatment time from 72 to 48 hr while obtaining high decellularization efficiencies, which corroborates our anecdotal observation that negative pressure speeds decellularization (Xu et al, ).…”
Section: Resultssupporting
confidence: 77%
“…The efficacy of decellularization agents greatly fluctuates with the tissue being treated. For instance, while TX is able to decellularize cartilage, corneal decellularization studies have shown great variability . Du et al found that decellularization of pig corneas using TX was unachievable, regardless of high concentrations (5% w/v) and prolonged time (96 hours).…”
Section: Decellularization Methodsmentioning
confidence: 99%
“…[47,5661] Decellularized or demineralized native matrices have also been used to engineer the enthesis. [48,59,60,62,63] …”
Section: Materials Processing Methodsmentioning
confidence: 99%
“…[150] Decellularized and demineralized bone matrix applied to the tendon-to-bone surgical suture site improved tendon-to-bone healing, demonstrated through increased amounts of fibrocartilage and mineralized fibrocartilage in the repair site enthesis and reduced rates of tendon failure. [63] Recent work has successfully decellularized the entire tendon-to-bone insertion, [62] with significant improvements in pullout strength using the decellularized tendon-to-bone insertion over the direct suture technique. [151] Cells were able to repopulate the graft and exhibited a transition from a cartilage-like to tenocyte-like morphology across the interface.…”
Section: Biochemical Factorsmentioning
confidence: 99%